2015
DOI: 10.1021/acs.oprd.5b00312
|View full text |Cite
|
Sign up to set email alerts
|

Applications of TiCl3 as a Diagnostic Reagent for the Detection of Nitro- and N-Oxide-Containing Compounds as Potentially Mutagenic Impurities Using Ultrahigh-Performance Liquid Chromatography Coupled with High-Resolution Mass Spectrometry

Abstract: The ICH has strict guidelines for limiting the presence of potentially mutagenic impurities (PMIs) in marketed drugs. Therefore, it is important to fully characterize and quantitate all possible PMIs that could arise during the process of synthesizing and developing a drug. Two important and prevalent examples of PMIs are compounds containing N-oxide and nitro functional groups. TiCl 3 derivatization is an established method for determining the presence or absence of N-oxide metabolites by reduction to the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…An assessment of impurities, metabolites, extractable and leachables showed that many contain aromatic N-oxides (15). For example, aromatic N-oxide-containing compounds are used as reagents (16).…”
Section: Introductionmentioning
confidence: 99%
“…An assessment of impurities, metabolites, extractable and leachables showed that many contain aromatic N-oxides (15). For example, aromatic N-oxide-containing compounds are used as reagents (16).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] In addition, LC-MS/MS methods used alone or in conjunction with derivatization techniques have been the preferred options for low-level analysis of potential mutagenic impurities (PMI). [16][17][18][19][20][21][22][23][24][25] However, direct analysis by single-quadruple mass spectrometry has been rarely used for this purpose, 7,26,27 although LC-MS method in conjunction with derivatization technique has been reported. 28 This paper discusses a chiral reversed-phase LC method coupled with single-quadruple mass spectrometry in selected ion monitoring mode (LC-MS SIM) 29 for direct stereoisomer analysis, which provided sufficient chiral quality control at low ppm level.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral liquid chromatography coupled with tandem mass spectrometry (LC‐MS/MS) has been widely used for low‐level detection in environmental7, 8 and pharmaceutical analysis, especially in the area of drug metabolism studies 9–15 . In addition, LC‐MS/MS methods used alone or in conjunction with derivatization techniques have been the preferred options for low‐level analysis of potential mutagenic impurities (PMI) 16–25 . However, direct analysis by single‐quadruple mass spectrometry has been rarely used for this purpose, 7,26,27 although LC‐MS method in conjunction with derivatization technique has been reported 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography coupled with electron ionization mass spectrometry (MS) has been commonly used to identify and quantitate different PMIs in complex mixtures. , However, this method often requires derivatization of the compounds, which is time-consuming and can lead to complications. Although high-performance liquid chromatography coupled with soft ionization mass spectrometry has become the gold standard for mixture analysis, ,, authentic compounds are required to unambiguously identify the compounds in the mixture.…”
Section: Introductionmentioning
confidence: 99%